Selenoprotein genetic variants may modify the association between serum selenium and oral cancer risk. (10th June 2020) - Bao, Xiaodan; Yan, Lingjun; Lin, Jing; Chen, Qing; Chen, Lin; Zhuang, Zhaocheng; Wang, Rui; Hong, Yihong; Qian, Jiawen; Wang, Jing; Chen, Fa; Liu, Fengqiong; et al.
Abstract: Objective: The relationship between selenium (Se) and oral cancer is still controversial, and the selenoprotein genes play crucial roles in selenium metabolism. We aim to investigate the potential effect of selenoprotein genes (including GPx and TXNRD ) in the association of serum Se with oral cancer risk. Methods: A case–control study including 235 oral cancer cases and 406 controls from September 2011 to December 2018 was conducted in Fujian, China. The peripheral blood samples were obtained from each participant. Genotyping was performed by MassARRAY system, and serum Se levels were measured by inductively coupled plasma mass spectrometry (ICP‐MS). Results: Compared with the lowest tertile of Se concentration, those with Se levels in the third tertile were associated with the lower risk of oral cancer (OR = 0.228; 95% CI: 0.135, 0.384). After additional adjustment for genetic risk score (GRS, derived from selenoprotein genetic variants), the model demonstrated the superior goodness of fit. When stratified by GRS, the negative correlation of serum Se was more pronounced among those with low risk (i.e., lower GRS). Moreover, there is a multiplicative interaction between serum Se and GRS for the risk of oral cancer ( p  = .001). Conclusions: The present study suggests that serum Se levels may be significantly associated with oral cancer risk, yet the association may be modified by the effects of selenoprotein genetic variants.